Micropapillary variant of mucinous carcinoma of the breast shows genetic alterations intermediate between those of mucinous carcinoma and micropapillary carcinoma. Issue 1 (13th June 2019) - Pareja, Fresia; Selenica, Pier; Brown, David N; Sebastiao, Ana P M; da Silva, Edaise M; Da Cruz Paula, Arnaud; Del, Angela; Fu, Li; Weigelt, Britta; Brogi, Edi; Reis‐Filho, Jorge S; Wen, Hannah Y
Abstract : Aims: Micropapillary variant of mucinous carcinoma of the breast (MPMC) is a rare histological form of oestrogen receptor (ER)‐positive invasive carcinoma that is characterised by micropapillary clusters of tumour cells in lakes of extracellular mucin. The aims of this study were to determine the genetic alterations underpinning MPMCs, and to determine whether they overlap with those of mucinous carcinomas and/or invasive micropapillary carcinomas. Methods and results: DNA from five MPMCs was subjected to whole‐exome sequencing. Somatic mutations, copy number alterations and mutational signatures were determined with state‐of‐the‐art bioinformatics methods. No mutations in genes significantly mutated in breast cancer, including TP53, PIK3CA, GATA3, and MAP3K1, were detected. We identified copy number alterations that have been reported in invasive micropapillary carcinomas, such as recurrent gains in 1q, 6p, 8q, and 10q, and recurrent losses in 16q, 11q, and 13q, as well as a recurrent 8p12–8p11.2 amplification encompassing FGFR1 . Like mucinous carcinomas, three of the five MPMCs analysed lacked PIK3CA mutations, 1q gains, and 16q losses, which are the hallmark genetic alterations of ER‐positive breast cancers, whereas two MPMCs harboured 16q losses and/or a complex pattern of copy number alterations similar to those found in breast‐invasive micropapillary carcinomas. Conclusions: MPMCs are heterogeneous at the genetic level; some tumours show a pattern of somatic genetic alterations similar to those of mucinous carcinomas, whereas others resemble invasive micropapillary carcinomas at the genetic level. These findings suggest that MPMCs may not constitute one histological subtype, but rather a convergent phenotype that can stem from mucinous carcinomas or invasive micropapillary carcinomas.